2016
DOI: 10.1519/jsc.0000000000001299
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of PARTwear Inertial Sensor and Optojump Optical Measurement System for Measuring Ground Contact Time During Running

Abstract: The aim of this study was to validate the detection of ground contact time (GCT) during running in two differently working systems: a small inertial measurement sensor, PARTwear (PW), worn on the shoe laces, and the optical measurement system, Optojump (OJ), placed on the track. Twelve well-trained subjects performed 12 runs each on an indoor track at speeds ranging from 3.0 -9.0 m·s-1. GCT of one step per run (total 144) was simultaneously obtained by the PW, the OJ, and a high-speed video camera (HSC), where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 37 publications
3
52
0
Order By: Relevance
“…There were no significant gait asymmetries when comparing GCTs of dominant and nondominant leg (P = .098) in the noninjured group, whereas in the previously injured group the GCTs of the injured side were significantly longer than the GCTs of the noninjured side (P < .001). The reported Borg values after the end of each session were on average 17.9 (range [16][17][18][19][20], indicating very hard to extremely hard exertion. Buildup of fatigue was therefore expected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no significant gait asymmetries when comparing GCTs of dominant and nondominant leg (P = .098) in the noninjured group, whereas in the previously injured group the GCTs of the injured side were significantly longer than the GCTs of the noninjured side (P < .001). The reported Borg values after the end of each session were on average 17.9 (range [16][17][18][19][20], indicating very hard to extremely hard exertion. Buildup of fatigue was therefore expected.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study demonstrated the validity and reliability of the device in the measurement of GCTs. 17 This method is feasible in field conditions in entire groups to gain insight into gait asymmetries, unlike other methods that rely on, for example, the braking impulse or joint angles, which are much more difficult to assess.…”
Section: Methodsmentioning
confidence: 99%
“…These studies differ in terms of sensor configuration, sensor location, and type of parameter measured [1]. Several groups have used inertial sensors in sprint running to characterize temporal parameters [2][3][4], body-segment orientation [5,6], ground reaction forces [7,8], and speed [9][10][11]. Surprisingly, only a few studies used MIMU to quantify spatiotemporal parameters in hurdle races.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, SL was quantified as the distance between the two GCT measured. The reliabi lity of the Optojump optical measurement system for measuring GCT and SL has been reported elsewhere [1,32]. Before the RSA test, players executed a standardised warm-up consisting of a 5 min low intensity run, 3 × 20 m progressive accelerations and a maximal 10 m sprint, separated by a 3 min rest.…”
Section: Repeated Sprint Ability (Rsa) Testmentioning
confidence: 99%